Determination of strains of Helicobacter pylori and of polymorphism in the interleukin-8 gene in patients with stomach cancer - VINAGRE, Ruth Maria Dias Ferreira (2015)
CONTEXT: Gastric neoplasia is the second most common cause of death by cancer in the world and H. pylori is classified as a type I human carcinogen by the World Health Organization. However, despite the high prevalence of infection by H. pylori around the world, less than 3% of individuals carrying the bacteria develop gastric neoplasias. Such a fact indicates that evolution towards malignancy may be associated with bacterial factors in the host and the environment. OBJECTIVES: To investigate the association between polymorphism in the region promoting the IL-8 (-251) gene and the H. pylori genotype, based on the vacA alleles and the presence of the cagA gene, using clinical and histopathological data. METHODS: In a prospective study, a total of 102 patients with stomach cancer and 103 healthy volunteers were analysed. Polymorphism in interleukin 8 (-251) was determined by the PCR-restriction fragment length polymorphism reaction and sequencing. PCR was used for genotyping the vacA alleles and the cagA in the bacterial strains PCR. Gastric biopsies were histologically assessed. RESULTS: The H. pylori serology was positive for 101 (99%) of all patients analysed, and 98 (97%) of them were colonized by only one strain. In patients with monoinfection, 82 (84%) of the bacterial strains observed had the s1b/m1 genotype. The cagA gene was detected in 74 (73%) of patients infected by H. pylori. The presence of the cagA gene was demonstrated as associated with the presence of the s1b/m1 genotype of the vacA gene (P = 0.002). As for polymorphism in the interleukin 8 (-251) gene we observed that the AA (P = 0.026) and AT (P = 0.005) genotypes were most frequent in the group of patients with gastric adenocarcinoma. By comparing the different types of isolated bacterial strains with the interleukin -8 (-251) and the histopathological data we observed that carriers of the A allele (AT and AA) infected by virulent strains (m1s1 cagA+) demonstrated a greater risk of presenting a degree of inflammation (OR = 24.75 CI 95% 2.29-267.20 P = 0.004) and increased neutrophilic activity (OR = 28.71 CI 95% 2.62-314 P = 0.002) in the gastric mucosa. CONCLUSION: Our results demonstrate that the interaction between polymorphism in the interleukin -8 (-251) gene, particularly with carriers of the A allele and the infecting type of H. pylori strain (s1m1 cagA positive) performs an important function in development of gastric adenocarcinoma.